The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.15173/esr.v15i2.508
|View full text |Cite
|
Sign up to set email alerts
|

Oil Price and the Dollar

Abstract: The aim of this paper is to test whether there is a stable long-term relationship between oil prices and the U.S. effective exchange rate, expressed in real terms. To this end, we perform co-integration and causality tests between the two variables. Our results show that causality runs from oil prices to the exchange rate. Moreover, as we investigate the channels through which oil prices affect the dollar exchange rate, we find out that the link between the two variables is transmitted through the U.S. net for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 20 publications
5
60
0
Order By: Relevance
“…Early research on the relationship between oil prices and exchange rates often used cointegration techniques and many studies have found evidence of an appreciation of the US dollar in response to rising oil prices (e.g., Amano and Van Norden, 1998a ;Bénassy-Quéré et al, 2007;Chen and Chen, 2007;and Coudert et al, 2008). Coudert et al (2008) find that real oil prices, the real US dollar effective exchange rate and US net foreign assets are cointegrated. Based on their analysis, oil prices affect exchange rates through the impact that oil prices have on US net foreign assets.…”
Section: Theoretical Considerations and Literature Reviewmentioning
confidence: 99%
“…Early research on the relationship between oil prices and exchange rates often used cointegration techniques and many studies have found evidence of an appreciation of the US dollar in response to rising oil prices (e.g., Amano and Van Norden, 1998a ;Bénassy-Quéré et al, 2007;Chen and Chen, 2007;and Coudert et al, 2008). Coudert et al (2008) find that real oil prices, the real US dollar effective exchange rate and US net foreign assets are cointegrated. Based on their analysis, oil prices affect exchange rates through the impact that oil prices have on US net foreign assets.…”
Section: Theoretical Considerations and Literature Reviewmentioning
confidence: 99%
“…Assuming that oil-exporting countries reinvest their revenues in US dollar assets, the dollar will appreciate in the short-run. However, the long-run reaction of the US dollar against other currencies is less clearcut and determined by the weight of oil in US total imports compared to the US weights in OPEC imports [Bénassy-Quéré et al, 2007;Coudert, Mignon and Penot, 2008]. Summing up the theoretical record, positive oil price shocks lead to a real appreciation (depreciation) of the exchange rates of oil-exporting (oil-importing) economies [Buetzer et al, 2012].…”
Section: Causalities Running From Oil Prices To Exchange Ratesmentioning
confidence: 99%
“…The relationship between the real oil price and real exchange rates against the US dollar has been analyzed for several countries in various studies covering diverse spans of data. Applying cointegration techniques, many authors have provided evidence of a real effective appreciation of the US dollar in the case of rising oil prices in the long-run [Amano and Van Norden, 1998b;Bénassy-Quéré et al, 2007;Coudert et al, 2008]. Clostermann and Schnatz [2000] focus on the real exchange rate of the dollar against the euro and also find indications of a real appreciation of the dollar in the case of a rise in real oil prices.…”
Section: Causalities Running From Oil Prices To Exchange Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that a portion of oil export revenues is recycled back in the US in the form of investment (real and financial) could result in a stronger dollar. See Coudert et al (2008) for a survey of theoretical and empirical work on the relationship between oil prices and exchange rates.…”
Section: Exchange Rate Channelmentioning
confidence: 99%